2021
DOI: 10.1007/s11356-021-16706-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of steel slag replaced mineral aggregate for road base/sub-base application based Vietnam and Japan standard

Abstract: Steelmaking slag is one of the most massive industrial by-products generated during steelmaking processes. This paper presents the current steelmaking slag production status and its potential to use as mineral aggregates in base/sub-base layer of road pavement. The mechanical properties of steelmaking slag were confirmed by the test method specified in Vietnam specification. The volume stability test of the slag was conducted based on JIS A 5015-2018 (Japanese Industrial Standard: Iron and steel slag for road … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Among the alternatives, it would be essential to identify sustainable materials with low global warming potential and a low environmental footprint, considering the climate change situation. Previous material property investigations in Vietnam have indicated that feasible materials to replace sand in the road construction sector, other than m-sand, include slags [37], ashes [38], and CDW [39,40]. The present study focuses on the environmental footprint and sheds light on the environmental impact of the extraction of primary raw materials in comparison to secondary raw materials as SBMs for the road subbase.…”
Section: Introductionmentioning
confidence: 94%
“…Among the alternatives, it would be essential to identify sustainable materials with low global warming potential and a low environmental footprint, considering the climate change situation. Previous material property investigations in Vietnam have indicated that feasible materials to replace sand in the road construction sector, other than m-sand, include slags [37], ashes [38], and CDW [39,40]. The present study focuses on the environmental footprint and sheds light on the environmental impact of the extraction of primary raw materials in comparison to secondary raw materials as SBMs for the road subbase.…”
Section: Introductionmentioning
confidence: 94%
“…A large number of scientific studies have been devoted to the problems of recycling industrial wastes of metallurgical production, including BFS [1][2][3][4][5][6]. A special place among the areas of research in the field of recycling blast-furnace and steel-smelting slags is occupied by the possibility of use these materials in construction and civil engineering [7][8][9][10][11][12][13][14][15][16][17][18][19][20], including production of cement [7][8][9], mortars, slag-alkaline binders [10,11], concrete [12][13][14], fine and coarse aggregates [15][16][17], mineral wool [18], ceramic paving stones [19], geopolymers [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nickel slag (NS) is a waste product from the nickel industry, which can be incorporated with other natural resources to enhance specific characteristics for various applications. 1 The high magnetite content of NS is the primary reason for its use in the absorption of electromagnetic interference (EMI) emissions, 2 sensors, 3 batteries, 4 alkaline activations, 5 and shielding. 6 Fayalite is a perovskite-type material that can be extracted from NS with useful properties, such as ferromagnetism, ferroelectricity, and superconductivity.…”
Section: Introductionmentioning
confidence: 99%